Epidemiological analysis of deaths from ectopic pregnancy in Brazil between 2010 and 2023 (Research, Society and Development, 2025)
Introduction: Ectopic pregnancy (EP) is characterized as an abnormal process of blastocyst implantation outside the uterus, making this process a serious medical condition and the main cause of maternal mortality in the first gestational trimester. Objective: Analyze the socio-epidemiological profile of deaths from ectopic pregnancy in Brazil between 2010 and 2023, based on the DATASUS database. Methodology: Ecological study with time series and quantitative approach, based on data from the Mortality Information System (SIM). Results: The study demonstrates that between 2010 and 2023, maternal deaths in Brazil from ectopic pregnancy present a sociodemographic profile characterized by the prevalence of women of reproductive age between 30 to 39 years (n = 249; 42%), followed by women aged 20 to 29 years (n = 232 and 40%). Mixed-race women (n = 341; 58%) and white women (n = 148; 25%) with education between 8 to 11 years of study and single women (n = 357 and 61%) represented the group with highest mortality.